2013
DOI: 10.1002/ange.201305969
|View full text |Cite
|
Sign up to set email alerts
|

Click to Release: Instantaneous Doxorubicin Elimination upon Tetrazine Ligation

Abstract: Die schnellste Klick‐Reaktion, die hoch selektive Diels‐Alder‐Reaktion mit inversem Elektronenbedarf, wurde so modifiziert, dass sie selektive bioorthogonale Freisetzungen ermöglicht. Auf diese Weise führte die Reaktion eines Tetrazins mit einem wirkstoffgebundenen trans‐Cycloocten zur augenblicklichen Freisetzung des Wirkstoffs und von CO2 (siehe Schema). Eine mögliche Anwendung ist die chemisch ausgelöste Freisetzung und Aktivierung eines Wirkstoffs aus einem tumorgebundenen Antikörper‐Wirkstoff‐Konjugat.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
104
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(109 citation statements)
references
References 20 publications
5
104
0
Order By: Relevance
“…Work by Rossin and Versteegen et al. further demonstrated that even the planar chirality of the trans ‐cyclooctene ring influences its reactivity and stability in Diels–Alder reactions 14. 15 Initial trans ‐cyclooct‐4‐ene amino acids ( 2 , Scheme S2, Supporting Information)8 featured the trans double bond opposite the oxygen atom, connecting the ring to the amino acid (Scheme S2, Supporting Information).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Work by Rossin and Versteegen et al. further demonstrated that even the planar chirality of the trans ‐cyclooctene ring influences its reactivity and stability in Diels–Alder reactions 14. 15 Initial trans ‐cyclooct‐4‐ene amino acids ( 2 , Scheme S2, Supporting Information)8 featured the trans double bond opposite the oxygen atom, connecting the ring to the amino acid (Scheme S2, Supporting Information).…”
Section: Methodsmentioning
confidence: 99%
“…A drawback of the 2‐ene isomer for labeling purposes is that the bicyclic product of the [4+2] cycloaddition reaction with tetrazines (Figure 1A) can undergo β ‐elimination under certain conditions, to release the original lysine at the level of amino acids and intact proteins. This was used by Versteegen and co‐workers to release drugs and most recently to decage a lysine in a protein 14. 16 Obviously, for labeling approaches this reaction reduces the labeling efficiency and needs to be observed.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although conceptually attractive, these approaches suffer from slow reaction kinetics and the oxidative sensitivity of the phosphine reagent. The installation by Robillard and coworkers of a carbamate drug linkage next to the double bond of a trans-cyclooctene dienophile created a clever solution to these problems for antibody-drug conjugates (Versteegen et al, 2013). Fast tetrazine ligation was followed by facile rearrangement to the corresponding pyridazine with ejection of the allylic carbamate leaving group, thus releasing the drug only upon receipt of the bioorthogonal reaction signal (Figure 10E).…”
Section: B Bioorthogonal Conjugation Strategies and Applicationsmentioning
confidence: 99%
“…Bioorthogonal reactions are designed to take place in cells and organisms without interfering with biological functions . In the pursuit of exploiting such processes in cancer therapy, reactions and tools that were once exclusively used to synthesize drugs in chemistry labs have been recently adapted to perform such tasks in living systems . Chemotherapeutics as doxorubicin, 5FU, gemcitabine, floxuridine, vorinostat or nitric oxide precursors can be “manufactured” from inactive precursors in biological environments through a variety of bio‐independent processes, including click‐to‐release reactions and bioorthogonal organometallic catalysis.…”
Section: Introductionmentioning
confidence: 99%